AKTIFITAS BERMAIN DAN KEMAMPUAN MOTORIK SISWA KELAS VI SD INPRES PERUMNAS I WAENA - Tri Setyo Guntoro (JURNAL OLAHRAGA PAPUA, 2013)
Abstract: Playing Activities, Student of Motor Ability. This study aims to determine condition of play activity with motor skills of students. Sample was 60 students. Data were collected by questionnaires and tests, analyzed using percentage. The results showed the motor skills of students in the low category there are 66.6% students, 20% of students medium category, and 13.4% of students better, while the low activity category students play 56.7% of students, 26.7% of students medium category, and 16.6% of students good category. Keywords: play activities, motor skills students.